Astrometric detection of intermediate-mass black holes at the Galactic Centre. Issue 3 (1st October 2018) - Girma, Eden; Loeb, Abraham
Abstract: We assess the astrometric detectability of intermediate-mass black holes populating the inner parsec of the Milky Way Galaxy. The presence of these objects induces dynamical effects on Sgr A* and the star S2, which could be detected by next generation astrometric instruments that enable microarcsec astrometry. An allowed population of ten 10 4 M⊙ intermediate-mass black holes within one parsec induces an angular shift of 65 μ as yr^-1 on the position of Sgr A*, corresponding to a perpendicular velocity component magnitude of1.6 km s^-1 . It also induces changes in the orbit of S2 that surpass those induced by general relativity but lie within observational constraints, generating a mean angular shift in periapse and apoapse of 62 and 970 µas, respectively.